2022
DOI: 10.1007/s11356-022-22756-9
|View full text |Cite
|
Sign up to set email alerts
|

Construction of direct Z-scheme g-C3N4/BiYWO6 heterojunction photocatalyst with enhanced visible light activity towards the degradation of methylene blue

Abstract: Construction of the Z-scheme heterojunction photocatalyst achieved highly improved photocatalytic ability by its high redox ability of the photoinduced e − -h + pairs. In the study, Z-scheme g-C 3 N 4 /BiYWO 6 heterojunction photocatalyst is prepared by the single step hydrothermal method. Further, its photocatalytic ability was assessed by degrading methylene blue under visible light exposure. Particularly, the optimized 30 wt. % of g-C 3 N 4 in the g-C 3 N 4 /BiYWO 6 composite exposes almost complete degrada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…As a result, the E CB potentials of pure WS 2 and BiOI are −0.418 and 0.541 eV, respectively. The flat band potentials of pure BiOI and WS 2 were governed by the following Equation 3: [34–37] E(RHE)=E(Ag/AgC1)+E(Ag/AgCl)+0.059pH $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr {\rm E}({\rm RHE})={\rm E}({\rm Ag}/{\rm AgC1})+{\rm E}({\rm Ag}/{\rm AgCl})+0.059\mskip4mu {\rm pH}\hfill\cr}}$ …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the E CB potentials of pure WS 2 and BiOI are −0.418 and 0.541 eV, respectively. The flat band potentials of pure BiOI and WS 2 were governed by the following Equation 3: [34–37] E(RHE)=E(Ag/AgC1)+E(Ag/AgCl)+0.059pH $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr {\rm E}({\rm RHE})={\rm E}({\rm Ag}/{\rm AgC1})+{\rm E}({\rm Ag}/{\rm AgCl})+0.059\mskip4mu {\rm pH}\hfill\cr}}$ …”
Section: Resultsmentioning
confidence: 99%
“…As a result, the E CB potentials of pure WS 2 and BiOI are À 0.418 and 0.541 eV, respectively. The flat band potentials of pure BiOI and WS 2 were governed by the following Equation ( 3): [34][35][36][37] EðRHEÞ ¼ EðAg=AgC1Þ þ EðAg=AgClÞ þ 0:059 pH (3)…”
Section: Radical Scavenging Studiesmentioning
confidence: 99%
“…Furthermore, BBSc Z-scheme heterojunction photocatalysts for the removal of organic dye pollutants are summarized in Table . Based on several report studies, it is evident that Bi-based Z- scheme heterojunctions hold great promise for the efficient degradation of dyes in wastewater treatment processes, offering a feasible solution to address the environmental concerns associated with dye pollution. The utilization of Bi-based Z-scheme heterojunctions has shown great potential in the degradation of dyes, with significantly improved photocatalytic performance and higher degradation efficiency compared to single component photocatalysts …”
Section: Bbzsh Photocatalytic Degradationmentioning
confidence: 99%
“…125 Furthermore, the optimized composition of g-C 3 N 4 /BiYWO 6 heterojunction photocatalysts has shown significant improvement in the degradation of methylene blue under visible light exposure, indicating its potential for wastewater remediation works. 126 Furthermore, Zhong and his colleagues utilized a In another study reported by Hao et al a ternary Z-scheme heterojunction of WO 3 /Ag 3 PO 4 /Bi 2 WO 6 photocatalyst was fabricated via a one-pot hydrothermal method for degradation RhB. 128 The result shows that, the Z-scheme heterojunction photocatalysts were shown an outstanding photocatalytic degradation rate constant of 1.9 and 1.3 times higher than that of pure Bi 2 WO 6 and WO 3 −Bi 2 WO 6 photocatalysts, respectively.…”
Section: ■ Photocatalytic Degradation Mechanisms In Z-and S-scheme He...mentioning
confidence: 99%
See 1 more Smart Citation